2017
DOI: 10.18632/oncotarget.18099
|View full text |Cite
|
Sign up to set email alerts
|

Integrative bioinformatics analysis identifies ROBO1 as a potential therapeutic target modified by miR-218 in hepatocellular carcinoma

Abstract: Patients diagnosed with advanced hepatocellular carcinoma (HCC) presented poor prognosis and short survival time. Althouth accumulating contribution of continuous research has gradually revealed complex tumorigenesis mechanism of HCC with numerous and jumbled biomarkers, those specific ones for HCC diagnose and therapeutic treatment are required illustration. Multiple genes over-expressed in HCC specimens with at least 1.5 fold change were cohorted, compared with the non-cancerous tissues through integrative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…GO term analysis revealed that ROBO1was involved in cell proliferation, adhesion and migration, and cell cycle regulation. Previous studies have also reported that ROBO1 is a target of miR-218 in certain types of cancer, such as hepatocellular carcinoma, glioma and nasopharyngeal cancer (21,46,47); however, the present study only predicted and confirmed it as a target gene of miR-218 in cervical cancer cells via RT-qPCR analysis. Therefore, future studies are required to investigate the regulation of ROBO1 by miR-218 and the downstream gene pathways.…”
Section: Discussioncontrasting
confidence: 91%
“…GO term analysis revealed that ROBO1was involved in cell proliferation, adhesion and migration, and cell cycle regulation. Previous studies have also reported that ROBO1 is a target of miR-218 in certain types of cancer, such as hepatocellular carcinoma, glioma and nasopharyngeal cancer (21,46,47); however, the present study only predicted and confirmed it as a target gene of miR-218 in cervical cancer cells via RT-qPCR analysis. Therefore, future studies are required to investigate the regulation of ROBO1 by miR-218 and the downstream gene pathways.…”
Section: Discussioncontrasting
confidence: 91%
“…The large‐scale genome analyses have revealed the molecular characteristics associated with HCC OS . However, most studies focused on miRNA, mRNA, gene, and protein expression . With knowledge growing, the functional role of lncRNAs in tumorigenesis and development also represents a significant untapped resource for HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] However, most studies focused on miRNA, mRNA, gene, and protein expression. [26][27][28][29][30] T A B L E 3 (Continued) growing, the functional role of lncRNAs in tumorigenesis and development also represents a significant untapped resource for HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have demonstrated that ROBO1 functions as a promoter of cell proliferation (19). It has also been observed that the expression of miR-218 has an inhibitory effect on cell proliferation and metastasis (19,20). These previous findings suggested that the expression of miR-218 suppressed cell proliferation and metastasis by targeting ROBO1.…”
Section: Human Circular Rna-0054633 Regulates High Glucose-induced Vamentioning
confidence: 93%
“…ROBO1, also known as protein SAX3, is the receptor of slit guidance ligand 1 (SLIT1) and SLIT2, which are associated with cell migration. In addition, several studies have demonstrated that ROBO1 functions as a promoter of cell proliferation (19). It has also been observed that the expression of miR-218 has an inhibitory effect on cell proliferation and metastasis (19,20).…”
Section: Human Circular Rna-0054633 Regulates High Glucose-induced Vamentioning
confidence: 99%